Digital image correlation based characterization of rubber material at large shear deformations in an extended temperature range. Issue 3 (4th May 2022) - Kanzenbach, Lars; Lehmann, Thomas; Ihlemann, Jörn
Abstract: This contribution deals with a new shear device, which is applied for rubber measurements in simple shear in an extended temperature range. As a special feature for the loading system, no bonding technique, or vulcanization is used, but a form fit connection via pins. The measured stress–shear value curves for different temperature levels are evaluated with a standard method from GOM ARAMIS. In addition, a new approximation based evaluation method is introduced and applied for shear value determination including smoothing of the raw digital image correlation data with consideration of characteristic noise properties. This enables the analysis of noise induced error influences. It was proved by the approximation based method, that the standard ARAMIS evaluation provides shear value results, which are suitable for performed characterization tests. As a consequence, the nearly homogeneous measurement data can be used for parameter fitting of constitutive rubber models.